2017
DOI: 10.1371/journal.pone.0187026
|View full text |Cite
|
Sign up to set email alerts
|

Corneal transplantation at Tenwek Hospital, Kenya, East Africa: Analysis of outcomes and associated patient socioeconomic characteristics

Abstract: PurposeTo review the graft survival rate, visual outcomes, and patient demographics of primary penetrating keratoplasty performed at Tenwek Hospital, a mission hospital in rural Kenya.MethodsA retrospective review was performed of the clinical records of patients who underwent primary penetrating keratoplasty for optical purposes from January 2012 to October 2014. The graft survival rates were constructed using the Kaplan-Meier method, and the effect of clinical and socioeconomic characteristics on time to gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This was expected as the symptom of blurred vision was previously cited as the chief presenting complaint amongst KC patients in studies conducted in Kenya. 9,10 However, Doreen et al 7 reported that the majority of patients in their study in Ghana complained of itching as the chief complaint. In this study, it could be that since patients presented when the KC was at an advanced stage with significant vision reduction, allergic complaints were less debilitating and hence of less concern as compared to reduced vision.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This was expected as the symptom of blurred vision was previously cited as the chief presenting complaint amongst KC patients in studies conducted in Kenya. 9,10 However, Doreen et al 7 reported that the majority of patients in their study in Ghana complained of itching as the chief complaint. In this study, it could be that since patients presented when the KC was at an advanced stage with significant vision reduction, allergic complaints were less debilitating and hence of less concern as compared to reduced vision.…”
Section: Discussionmentioning
confidence: 90%
“…A single facility-based study that analyzed the characteristics of 254 KC cases reported children as young as 6 years-old presenting with clinical signs. 9 Further, Chen et al 10 reported KC as the leading cause of corneal transplantation and other surgical interventions in Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…The authors hypothesize that this finding may be related to poor patient compliance in the former group. 41…”
Section: Discussionmentioning
confidence: 99%
“…Both patient age and preoperative diagnosis as independent factors, as well as with and without their interaction, were not statistically significant at the 0.05 level. This is likely because in the previously reported data, 11 of the 13 (84.6%) patients diagnosed with PBK were over 60 years of age; whereas, only 4 of the 26 (15.4%) patients diagnosed with corneal scar and 1 of the 78 (1.3%) patients diagnosed with keratoconus were over 60 years of age [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes of PKP at Tenwek Hospital, a tertiary care mission hospital in a rural low-resource setting located approximately 240 kilometers (4 hours) west of Nairobi, were previously reported [ 4 ]. While this study reported a favorable rate of improvement in uncorrected visual acuity and a favorable one-year graft survival rate, a significant percentage of the patient population (33.9%) was lost to follow-up (LTFU) at one year.…”
Section: Introductionmentioning
confidence: 99%